Direction Identification System of Garlic Clove Based on Machine Vision - Gao Chi; Gao Hui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to fulfill the requirements of seeding direction of garlic cloves, the paper proposed a research method of garlic clove direction identification based on machine vision, it expounded the theory of garlic clove direction identification, stated the arithmetic of it, designed the direction identification device of it, then developed the control system of garlic clove direction identification based on machine vision, at last tested the garlic clove direction identification, and the result of the experiment certificated that the rate of garlic clove direction identification could reach to more than 97%, and it demonstrated that the research is of high feasibility and technological values. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2456